(untitled) (Modern American Journal of Biological and Environmental Sciences, 2026)
Blended learning has become an increasingly important approach in modern education by combining traditional face-to-face instruction with digital learning technologies. In biology education, blended learning provides opportunities to improve conceptual understanding, student engagement, and flexibility in the learning process. This theoretical article examines the effectiveness of blended learning in teaching biology through the analysis of educational theories and existing literature.